Psychoanalysis and public policies of mental health in chile: universality, diversity and singularity - Aveggio, Ricardo (Estado, Gobierno y Gestión Pública, 2018)
This article reviews the public policies of mental health in Chile and their insertion in the Chilean health system. It discusses the ideological tensions that arise from the implementation of these in the context of neoliberalism and a subsidiary state. It introduces the psychoanalytic conception of suffering and its relations with the political, relating it to the structure of the social bond and the cultural diversity approach. It analyzes the implications of the difference between diversity and uniqueness, proposing some reflections on what the practice of psychoanalysis can contribute to the development of public policies on mental health.